Extent of compliance with COVID-19 prevention and control guidelines among supermarkets in Kampala Capital City and Mukono Municipality, Uganda. - Richard K Mugambe; Tonny Ssekamatte; Stevens Kisaka; Solomon T Wafula; John Bosco Isunju; Aisha Nalugya; Patience Oputan; Douglas Kizito Makanga; Michael Mukiibi; Esther Buregyeya; Simon Kasasa; Winnifred K Kansiime; et al. (PLoS ONE)
Background Despite the development and enforcement of preventive guidelines by governments, COVID-19 continues to spread across nations, causing unprecedented economic losses and mortality. Public places remain hotspots for COVID-19 transmission due to large numbers of people present; however preventive measures are poorly enforced. Supermarkets are among the high-risk establishments due to the high interactions involved, which makes compliance with the COVID-19 preventive guidelines of paramount importance. However, until now, there has been limited evidence on compliance with the set COVID-19 prevention guidelines. Therefore, this study aimed to measure compliance with the COVID-19 prevention guidelines among supermarkets in Kampala Capital City and Mukono Municipality Uganda. Methods A cross-sectional study was conducted among selected supermarkets in Kampala Capital City and Mukono Municipality in September 2020. A total of 229 supermarkets (195 in Kampala City and 34 in Mukono Municipality) were randomly selected for the study. Data were collected through structured observations on the status of compliance with COVID-19 prevention guidelines, and entered using the KoboCollect software, which was preinstalled on mobile devices (smart phones and tablets). Descriptive statistics were generated to measure compliance to the set COVID-19 Ministry of Health prevention guidelines using Stata 14 software. Results Only 16.6% (38/229) of the supermarkets complied with the COVID-19 prevention and control guidelines. In line with the specific measures, almost all supermarkets 95.2% (218/229) had hand washing facilities placed at strategic points such as the entrance, and 59.8% (137/229) of the supermarkets surveyed regularly disinfected commonly touched surfaces. Only 40.6% and 30.6% of the supermarkets enforced mandatory hand washing and use of face masks respectively for all customers accessing the premises. Slightly more than half, 52.4% (120/229) of the supermarkets had someone or a team in charge of enforcing compliance to COVID-19 measures and more than half, 55.5% (127/229) of the supermarkets had not provided their staff with job-specific training/mentorship on infection prevention and control for COVID-19. Less than a third, 26.2% (60/229) of the supermarkets had an infrared temperature gun for screening every customer, and only 5.7% (13/229) of the supermarkets captured details of clients accessing the supermarket as a measure to ease follow-up. Conclusion This study revealed low compliance with COVID-19 guidelines, which required mandatory preventive measures such as face masking, regular disinfection, social distancing, and hand hygiene. This study suggests the need for health authorities to strengthen enforcement of these guidelines, and to sensitise the supermarket managers on COVID-19 in order to increase the uptake of the different measures.